Antecedents of the client's trust in low- versus high-consequence decisions. Issue 1 (9th February 2015) - Terres, Mellina da Silva; dos Santos, Cristiane Pizzutti; Basso, Kenny
Abstract : Purpose: – The purpose of this study is to address the role of high- and low-consequence exchanges in the relationship between trust and its antecedents (i.e., affective and cognitive elements) and consequences (i.e., positive WOM and search for second opinion intentions) in the context of the provision of medical services. Design/methodology/approach: – We performed a survey with 681 patients from a large hospital. The data were analyzed through a multigroup structural equation approach. Findings: – Findings show that during service encounters affective aspects have greater impact on consumer trust in situations of high-consequence than in low-consequence exchanges, while cognitive aspects have greater impact when consequences are low than when they are high. In addition, the authors found that the more severe the consequences, the greater the impact of trust on positive WOM and search for second opinion intentions. Originality/value: – This study is the first to consider the exchange consequences as an important moderator of the relationship between trust and affection and cognition elements involved in client-service provider encounters. Overall, the findings show higher importance of affective aspects (compared to cognitive aspects) for the formation of trust, in situations in which the individual perceives the consequences of their exchanges as severe.